Matrix metalloproteinases-9 and tissue inhibitor of matrix metalloproteinases-1 in sarcoidosis patients - Ivanišević Jasmina; Stefanović Aleksandra; Kotur-Stevuljević Jelena; Jelić-Ivanović Zorana; Spasić Slavica; Videnović-Ivanov Jelica; Mihailović-Vučinić Violeta (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Matrix metaloproteinases (MMPs) and their specific inhibitors - tissue inhibitors of matrix metalloproteinases (TIMPs) play an important role in pulmonary extracellular matrix destruction. Sarcoidosis is an inflammatory disease affecting multiple organs. It has been reported that MMP-9 and TIMP-1 levels were increased in bronchoalveolar lavage fluid and induced sputum of sarcoidosis patients. The aim of our study was to evaluate MMP-9, TIMP-1 and MMP-9/TIMP-1 complex concentrations and MMP-9/TIMP-1 ratio in sarcoidosis patients, their relationship with inflammatory markers and their ability do predict the existence of disease. We included 101 sarcoidosis patients and 50 healthy subjects. Serum samples were analyzed. Besides routine biochemical parameters, high-sensitive C-reactive protein (hsCRP), serum amyloid A (SAA), MMP-9, TIMP-1 and MMP-9/TIMP-1 complex concentrations were measured. MMP-9 (P<0.05), hsCRP, SAA and TIMP-1 (P<0.001) concentrations were significantly increased in patients whereas MMP-9/TIMP-1 complex was higher in patients, but with marginal significance. In sarcoidosis, TIMP-1 correlated significantly positively with inflammatory parameters (P<0.05). Uni-variate analysis showed that MMP-9, TIMP-1, hsCRP and SAA had the ability to predict the existence of sarcoidosis. In the model consisted of MMP- 9, TIMP-1, hsCRP and SAA, only SAA remained significant predictor of disease (P<0.01). Results showed the significance of MMP-9 and TIMP-1 in sarcoidosis.